Capital Budgeting pada Proyek Teknologi 5G - Tomy Aji Nuraidi (Jurnal Manajemen Bisnis dan Kewirausahaan, 2021)
The development of digital business and internet technology in the telecommunications industry in Indonesia became a challenge for telecommunications companies, one of which is PT. Telkom Tbk. One study of the strategies that the author carefully regarding the analysis of Capital Budgeting on the 5th Generation (5G) technology project on PT. Telkom Indonesia (Persero) Tbk. and PT Telkomsel Tbk that using the cost benefit method. This study aims to provide a capital budgeting analysis to develop 5G network investment in Indonesia and assess investment feasibility. By using Payback Period calculation, Net Cash Flow and Internal Rate of Return can be identified the potential investment feasibility based on the value of the calculation and then the investment feasibility can be compared. The results show that the calculation of the payback period yields a value of 1.63 years. Whereas the calculation of net present value yields a value of Rp. 189,267 Trillion. For the average rate of return method, the ARR value is 1490.96%. Based on this value, it can be obtained that the 5G network investment project is feasible to be carried out by PT Telkom Tbk and PT Telkomsel companies.  Perkembangan bisnis digital dan teknologi internet pada industry telekomunikasi di Indonesia menjadi tantangan tersendiri bagi perusahaan telekomunikasi salah satunya PT. Telkom Tbk. Salah satu kajian strategi yang penulis teliti mengenai analisis Capital Budgeting pada proyek teknologi 5 th Generation (5G) PT. Telkom Indonesia (Persero) Tbk. dan PT Telkomsel Tbk dengan menggunakan metode cost benefit. Penelitian ini bertujuan memberikan analisis capital budgeting guna mengembangkan investasi jaringan 5G di negara Indonesia dan menilai kelayakan investasi. Dengan menggunakan perhitungan Payback Period, Net Cash Flow dan Internal Rate of Return dapat diidentifikasi potensi kelayakan investasi berdasarkan nilai perhitungan tersebut dan selanjutnya dapat dibandingakan kelayakan investasi. Hasil menunjukkan untuk perhitungan payback period menghiasilkan nilai 1.63 tahun. Sedangkan perhitungan net present value menghasilkan nilai RP 189.267 Triliun. Untuk metode average rate of return nilai ARR adalah 1490,96%. Dengan berdasarkan nilai tersebut dapat diperoleh bahwa proyek investasi jaringan 5G layak dilakuakn perusahaan PT Telkom Tbk dan PT Telkomsel.